Modelling behaviour of bridge pylon for test load using subspace method - Branko Milovanović; Stevan Marošan; Marko Pejić; Milutin Pejović (Geodetski Vestnik, 2015)
This paper presents the procedure of structure behaviour analysis and modelling applying the subspace method, which has been used in system identification but not in geodetic practice. This method enables the state space dynamic model parameters to be estimated. The equation error model has been used to form the dynamic system model. In addition, two pylons of the same bridge have been demonstrated to behave differently due to the position of the Sun. The entire system identification procedure has been demonstrated in modelling behaviour of the “Sloboda” bridge over the Danube pylon in direction of Novi Sad. The measurements were compiled during the bridge test load conducted in September 2005. The input signals subject to the analysis are the long-periodic signals: namely, the force in pylon cables and temperature. The output signals are pylon top displacements. The civil engineering experts' requirements called for identification of all displacements exceeding 10 mm. The pylon top position was determined by static GPS along with the 25- minute measurements per epoch.